2020
DOI: 10.1371/journal.pone.0235653
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Intensive Care Unit admission and outcomes among patients with coronavirus: A systematic review and Meta-analysis

Abstract: Background The rate of ICU admission among patients with coronavirus varied from 3% to 100% and the mortality was as high as 86% of admitted patients. The objective of the systematic review was to investigate the rate of ICU admission, mortality, morbidity, and complications among patients with coronavirus. Methods A comprehensive strategy was conducted in PubMed/Medline; Science direct and LILACS from December 2002 to May 2020 without language restriction. The Heterogeneity among the included studies was chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
219
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(241 citation statements)
references
References 61 publications
11
219
3
8
Order By: Relevance
“…Steroids were used in 58.9% (n = 33) and hydroxychloroquine in 12.5% (n = 7). The median length of hospitalization was 13 [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ] days. Specific characteristics from each patient group (0-10d vs. >10d) are demonstrated in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroids were used in 58.9% (n = 33) and hydroxychloroquine in 12.5% (n = 7). The median length of hospitalization was 13 [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ] days. Specific characteristics from each patient group (0-10d vs. >10d) are demonstrated in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the death rate found was 32%, which is higher than other general cohorts [ 20 ]. Nevertheless, given the high ICU admission rate, it is expected that outcomes results become closer to cohorts of critically-ill patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent data, an unfavorable progression of SARS-CoV-2 infection, such as needing mechanical ventilation and intensive care unit (ICU) admission, occurs in over 30% of patients, and it is then associated with a mortality rate approximating 40% [ 3 ]. Therefore, the identification of demographic, clinical, radiological, and laboratory predictors of unfavorable disease progression must be considered a priority for current clinical and translational research on COVID-19, as this will enable a timely, tailored, and more aggressive treatment for those patients who may have an increased risk of developing severe or critical disease.…”
Section: Introductionmentioning
confidence: 99%
“…0.9% to 32% of these patients require admission to intensive care units (ICU) for advanced respiratory support. [1][2][3][4] A surge in critically ill patients with respiratory failure has overwhelmed ICU capacity in many healthcare systems across the world. Studies published during the early phase of the pandemic have showed poor outcomes in invasively ventilated COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%